L’identité professionnelle de futurs enseignants de l’école primaire au prisme des langues-cultures - Séverine Behra; Agathe Chassard; Hélène Erikson; Églantine Guely Costa; Dominique Macaire; Kossi Seto Yibokou (Recherches en didactique des langues et des cultures)
Teachers’ professional identity is a component of professionality closely linked to students’ learning. It is both a provisional state and a living process (Gohier et al., 2001). Due to their disciplinary and cross-disciplinary dimensions, languages and cultures contribute to research into professional identity as a dynamic system (Cicurel, 2011; Muller, 2021). The professional identity of teachers of (foreign) languages and cultures deserves to be considered in the light of diverse multilingual and societal contexts, as well as the issues linked to every student’s academic achievement, as suggested by recent international reports (OECD, 2022).Our study is based on the end-of-module assessment of language didactics students in the first year of a master’s degree in primary education (in France). The assessment situation invited the students to reflect on their future professional activity by highlighting the role of languages and cultures. We analyzed the range of interrelationships between the various indicators derived from the examination papers in order to reveal traces of a professional identity and their unique manifestations for these students.